Sequence-dependent backbone dynamics of a viral fusogen transmembrane helix - Stelzer, Walter (Wiley Subscription Services, Inc., A Wiley Company, 2012)
The transmembrane domains of membrane fusogenic proteins are known to contribute to lipid bilayer mixing as indicated by mutational studies and functional reconstitution of peptide mimics. Here, we demonstrate that mutations of a GxxxG motif or of Ile residues, that were previously shown to compromise the fusogenicity of the Vesicular Stomatitis virus G-protein transmembrane helix, reduce its backbone dynamics as determined by deuterium/hydrogen-exchange kinetics. Thus, the backbone dynamics of these helices may be linked to their fusogenicity which is consistent with the known over-representation of Gly and Ile in viral fusogen transmembrane helices. The transmembrane domains of membrane fusogenic proteins are known to contribute to lipid bilayer mixing. Our present results demonstrate that mutations of certain residues, that were previously shown to compromise the fusogenicity of the Vesicular Stomatitis virus G-protein transmembrane helix, reduce its backbone dynamics. Thus, the data suggest a relationship between sequence, backbone dynamics, and fusogenicity of transmembrane segments of viral fusogenic proteins.